Stimulating parietal regions of the multiple-demand cortex impairs novel vocabulary learning. (12th November 2021) - Sliwinska, Magdalena W.; Elson, Ryan; Pitcher, David
Abstract: Neuroimaging research demonstrated that the early stages of learning engage domain-general networks, non-specialist brain regions that process a wide variety of cognitive tasks. Those networks gradually disengage as learning progresses and learned information becomes processed in brain networks specialised for the specific function (e.g., language). In the current study, we used repetitive transcranial magnetic stimulation (rTMS) in the form of continuous theta burst stimulation (cTBS) to test whether stimulation of the bilateral parietal region of the domain-general network impairs learning new vocabulary, indicating its causal engagement in this process. Twenty participants, with no prior knowledge of Polish, learned Polish words for well-known objects across three training stages. The first training stage started with cTBS applied to either the experimental domain-general bilateral parietal site or the control bilateral precentral site. Immediately after cTBS, the vocabulary training commenced. A different set of words was learned for each site. Immediately after the training stage, participants performed a novel vocabulary test, designed to measure their knowledge of the new words and the effect of stimulation on learning. To measure stimulation effect when the words were more established in the mental lexicon, participants received additional training on the same words but without cTBS (second training stage) and then the full procedures from the first training stage were repeated (third training stage). Results demonstrated that stimulation impaired novel word learning when applied to the bilateral parietal site at the first stage of learning only. This effect was not present when newly learned words were used more proficiently in the third training stage, or at any learning stage during control site stimulation. Our results show that the bilateral parietal region of the domain-general network causally contributes to the successful learning of novel words. Highlights: Learning engages domain-general regions of the Multiple Demand Cortex (MDC). TMS impaired word learning when applied to the bilateral parietal region of the MDC. The bilateral parietal MDC causally contributes to the successful learning.